Oropharyngeal candidiasis in HIV/AIDS patients and non-HIV subjects in the Southeast of Iran - Samira Salari; Pooya Ghasemi Nejad Almani; Abbas Hosain pour (Mazandaran University of Medical Sciences, 2018)
Background and Purpose: Candida species are the common opportunistic pathogens during the course of human immunodeficiency virus (HIV) infection. Oropharyngeal candidiasis (OPC) is generally known as the initial sign of HIV infection. The aim of this study was to compare demographic characteristics and frequency of Candida species between HIV/AIDS patients and non-HIV subjects in Kerman, southeast of Iran. Materials and Methods: This study was conducted on 143 samples collected from the oral cavity of 81 HIV/AIDS patients and 35 non-HIV subjects. The samples were cultured on Sabouraud dextrose agar and CHROMagar. The identification of Candida species was accomplished using the color of colony and polymerase chain reaction-restriction fragment length polymorphism. Results: According to the results, C. albicans (n=25, 69.14%) was the most prevalent species isolated from the HIV/AIDS patients, followed by C. glabrata (n=19, 23.46%). Other isolated species included C. parapsilosis (n=4, 4.94 %), C. krusei (n=1, 1.24%), and C. kefyr (n=1, 1.24%). Out of the 35 Candida species recovered from the oral samples of non-HIV subjects, 23 (65.71%) and 12 (34.29%) cases were C. krusei and C. albicans, respectively. Candida krusei was the only non-albicans species found in the non-HIV subjects that was also the predominant isolated species. Regarding the HIV/AIDS patients, the highest prevalence of OPC was observed in the age group of 41-50 years. However, in the non-HIV subjects, the age group of 31-40 years had the highest prevalence of this infection. Furthermore, no correlation was observed between the gender and number of Candida isolates. Conclusion: Consideration of the epidemiologic data showed that the two groups were significantly different in terms of the prevalence of Candida species, which could play a major role in the selection of effective drugs for the treatment of candidiasis.